Explaining and Predicting the Ocean Conveyor – the EPOC project - de Steur, Laura (Zenodo, 2023)
Presentation of the EPOC project at the " EC-ESA Joint Earth System Science Initiative " eventin the session "Polar I: The Arctic Ocean:Towards an Integrated view".